Privileging place: Reflections on involving people with dementia in a residency. (November 2015) - Bartlett, Ruth; Hick, Caroline; Houston, Agnes; Gardiner, Larry; Wallace, Daphne
Although attention is paid to involving people with dementia as collaborators in research, the issue of place – where involvement actually occurs – has been neglected. This is significant because we know from the academic literature that places can adversely affect social relations and a person's ability to participate as equal partners. This paper privileges place and documents our experiences of running residencies in the English Lake District with people with dementia – Houston, Gardiner and Wallace all have some form of dementia. In doing so we provide a model to reference for involving people with dementia in research and knowledge production, while simultaneously strengthening the evidence base for the residency as a method for participatory research. People with dementia participated in two residencies to co-produce a touring exhibition and educational resource as part of a research dissemination project. We found that by privileging place a more equitable, productive, healthier, and respectful way of involving people with dementia as collaborators in research dissemination could be realised. The project has wider implications for the involvement of people with dementia in not only research, but also public consultations, service evaluations, and policy-related work.